Production Factors and Commodity Prices on Farmers' Exchange Rate in Indonesia: Panel Data Analysis 2019–2023 - Nabila Prastyanti Putri Hanifah; Nur Hidayah (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research seeks to ascertain the components of agricultural production and the price dynamics of commodities that affect the Nominal Producer Price (NTP) in Indonesia, utilizing panel data from 26 provinces over the period from 2019 to 2023. The independent variables examined comprise labor, commodity prices, harvested land area, and farmer productivity. Through a series of model evaluations, the Fixed Effect Model (FEM) emerged as the optimal model, as determined by the outcomes of the Chow and Hausman tests. Collectively, all variables demonstrated a statistically significant impact on the NTP, with a coefficient of determination of 0.9681, signifying that 96.81% of the variability in the NTP can be attributed to these factors. On an individual basis, the labor variable exhibited a negative and significant influence, suggesting that an increase in the workforce has not been matched by corresponding improvements in work efficiency. In contrast, commodity prices displayed a positive and significant relationship, indicating that rising agricultural product prices can enhance farmer welfare. The variables pertaining to harvested area and farmer productivity revealed a positive yet insignificant impact on the NTP, implying that an increase in production alone does not necessarily translate into improved welfare without the backing of efficient distribution and price stability. These results highlight the necessity for policies aimed at price stabilization, enhancement of value addition, and modernization of agricultural practices to bolster farmers' purchasing power and overall welfare.